(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Rheumatoid arthritis (RA) is currently considered not only a chronic inflammatory joint disease but also a systemic autoimmune process, based on a complex interaction of genetic predisposition, immune dysregulation, and environmental triggers. Among the latter, microbial factors, primarily the mucosal microbiota and antigenic stimulation of bacterial and viral origin, are increasingly playing a significant role.This problem is particularly relevant given that, according to current understanding, autoimmune processes in RA often begin long before the clinical manifestation of arthritis. Autoantibodies, primarily ACPA, as well as signs of immune activation at the mucosal level, can be detected even at the preclinical stage. Therefore, research on microbial antigens and the humoral response to them goes far beyond the specific infectious hypothesis.